2019
DOI: 10.1186/s12955-019-1085-1
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life assessment for patients with advanced or metastatic renal cell carcinoma treated with a tyrosine kinase inhibitor using electronic patient-reported outcomes in daily clinical practice (QUANARIE trial): study protocol

Abstract: BackgroundTwo main therapies, pazopanib and sunitinib, are used in the first-line setting for metastatic renal cell carcinoma (mRCC). These two tyrosine kinase inhibitors (TKI) are equally effective in terms of survival; however, they frequently induce adverse events. In this setting, Health-Related Quality of life (HRQoL) is a key element in the choice between these two treatments and the evaluation of treatment effectiveness. It could be of interest to evaluate HRQoL in daily clinical practice to aid adequat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Moreover, to date, with the development of patient-reported outcome measures, we can contemplate collecting HRQOL information such as QLQ-C30 in daily clinical practice in the same way as in randomised clinical trials [41]. Some clinical trials have been conducted in France in the Franche-Comté region to assess the feasibility of collecting data in daily practice (data under analysis) [42]. This will allow having healthstate utility values obtained from QLQ-C30 for a specific population from which the CUA can be done.…”
Section: Quite a Bitmentioning
confidence: 99%
“…Moreover, to date, with the development of patient-reported outcome measures, we can contemplate collecting HRQOL information such as QLQ-C30 in daily clinical practice in the same way as in randomised clinical trials [41]. Some clinical trials have been conducted in France in the Franche-Comté region to assess the feasibility of collecting data in daily practice (data under analysis) [42]. This will allow having healthstate utility values obtained from QLQ-C30 for a specific population from which the CUA can be done.…”
Section: Quite a Bitmentioning
confidence: 99%
“…In addition, getting the patient to complete an HRQoL questionnaire before each consultation may be useful for the physician to assess any evolution of HRQoL and to identify any specific issues to be discussed. Different feasibility studies are underway to systematically collect ICI-related symptom and HRQoL data [ 39 , 40 ] and should provide interesting complementary information. A recent study on social media suggested that existing standard HRQoL questionnaires should be enriched with new items that are more relevant for patients treated with ICIs in their daily experience with disease and treatment [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 26 , 27 , 28 Several studies have focused on the feasibility and the interest of HRQoL questionnaires in routine practice, including the use of electronic monitoring-based or web-based approaches, but few studies have investigated the patient and clinician expectations regarding HRQoL management in France. 29 , 30 , 31 In addition, recent findings indicate that current standardised PRO questionnaires may have limitations in capturing all the patient relevant domains of HRQoL for patients treated with immunotherapies. 32 Notwithstanding the absence of a consensus on the ideal instruments for HRQoL assessment, both interview guides and questionnaires prove useful depending on which time point of the patient care pathway they are implemented and patient/physician preferences.…”
Section: Discussionmentioning
confidence: 99%